2012
DOI: 10.1016/j.funbio.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and metabolic profiles of Trichoderma strains isolated from common bean crops in the Brazilian Cerrado, and potential antagonism against Sclerotinia sclerotiorum

Abstract: Some species of Trichoderma have successfully been used in the commercial biological control of fungal pathogens, e.g., Sclerotinia sclerotiorum, an economically important pathogen of common beans (Phaseolus vulgaris L.). The objectives of the present study were (1) to provide molecular characterization of Trichoderma strains isolated from the Brazilian Cerrado; (2) to assess the metabolic profile of each strain by means of Biolog FF Microplates; and (3) to evaluate the ability of each strain to antagonize S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 31 publications
4
56
0
17
Order By: Relevance
“…VM are often considered a key mechanism in the biological control of seed-borne pathogens by fungal antagonists (Agüero et al, 2008;Lopes et al, 2012). However, the most efficient among our Trichoderma strains, CEN287, behaved similarly to the other strains regarding VM.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…VM are often considered a key mechanism in the biological control of seed-borne pathogens by fungal antagonists (Agüero et al, 2008;Lopes et al, 2012). However, the most efficient among our Trichoderma strains, CEN287, behaved similarly to the other strains regarding VM.…”
Section: Discussionmentioning
confidence: 82%
“…Confrontation plate assay is frequently used for screening of biological control agents (Carvalho et al, 2011b;Lopes et al, 2012). PCA analysis indicated that NVM were negatively correlated with confrontation plate assay.…”
Section: Discussionmentioning
confidence: 99%
“…As espécies identificadas são conhecidas e utilizadas no controle biológico de fitopatógenos habitantes do solo, inclusive para o controle de S. sclerotiorum (LOPES et al, 2012;RODRIGUES, 2010 Para a confrontação direta, os melhores resultados foram evidenciados pelos isolados CP21 e os armazenados, exceto TC1.15, uma vez que apresentaram nota igual ou inferior a 4, na escala de Bell (1982), enquanto os menos promissores foram os isolados do grupo SP, considerados pouco eficientes. Apesar dos isolados CP terem exibido a maior taxa de crescimento micelial apenas CP21 mostrou destaque na confrontação direta, sugerindo o envolvimento de mais de um mecanismo de ação, como liberação de metabólitos ou parasitismo.…”
Section: Resultados E Discussão Identificação Dos Isolados De Trichodunclassified
“…Sabe-se que a alface é a hortaliça folhosa mais consumida pela população brasileira, sendo produzida em todos os estados da federação (SALA; COSTA, 2012). Entretanto, apresenta alta suscetibilidade a diversas doenças fitopatogênicas, em especial a S. sclerotiorum, causadora de uma enfermidade popularmente conhecida como mofo-branco (LOPES et al, 2012), devido a presença de um micélio branco de aspecto cotonoso nas plantas infectadas. Em condições de alta umidade e temperaturas amenas os danos causados por S. sclerotiorum podem chegar a mais de 50% (CLARKSON et al, 2014), principalmente em viveiros de mudas, onde ocasionam o damping off ou tombamento de plântulas.…”
Section: Introductionunclassified
“…Baseando-se nos resultados da Tabela 1, apenas o isolado CEN288 se destacou quanto a produção de metabólitos voláteis, com valores médios de inibição superiores a 50%, semelhantemente aos verificados por Lopes et al (2012). A alta produção de antibióticos não voláteis não foi correlacionada à alta produção de inibidores voláteis.…”
Section: Materials E Métodos Isolados De Antagonistas E Patógenounclassified